Selecting for feed conversion - Schalles, R.R.; Blum, J.K.; Smith, W.H. (Kansas State University. Agricultural Experiment Station, 2011)
Selecting animals for decreased feed per unit of gain has made small changes in feed conversion over a four-year period. Adjusting for maintenance requirements by using mid weight to 0.75 power was not entirely satisfactory as that ignores differences in growth patterns. Favorable genetic relationships were found between feed conversion and most other economically important traits, especially yearling growth traits.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Feed; Gain; Growth